Oral health Attitude Knowledge Behavior and Consent towards Dental treatment among School children - Mathur, Aditi; Gupta, Tripti (Journal of Orofacial Research, 2011)
This study aims at determining the oral health awareness level, attitude, knowledge, behavior, pattern of dental health practice and consent towards their dental treatment as well as to evaluate the factors that determine these variables and their association with socioeconomic status. School children of age 8-15 years were recruited for this study. They are divided into two groups: high socioeconomic and low socioeconomic status. The subjects completed a questionnaire thataimed to evaluate school children’s behavior, knowledge, attitude, perception of their oral health and consent towards their dental treatment. 15.9% subjects found to brush their teeth twice in a day among high socioeconomic group and 9.9% among low socioeconomic. Among 22.5% of high socioeconomic and 8.6% of low socioeconomic group pain is the driving factor for dental visit. 13.2% and 11.3% of high and low socioeconomic class wants that they should be involved in decision making process about their treatment. The result of this study indicate that children and parents attitude ,awareness toward oral health need to beimproved irrespective of socioeconomic status of family but special attention must be given to low socioeconomic class. Comprehensive oral health education programs are required to achieve these goals.